2009
DOI: 10.1536/ihj.50.389
|View full text |Cite
|
Sign up to set email alerts
|

Half-Logistic Time Constants as Inotropic and Lusitropic Indices for Four Sequential Phases of Isometric Tension Curves in Isolated Rabbit and Mouse Papillary Muscles

Abstract: SummaryThe waveforms of myocardial tension and left ventricular (LV) pressure curves are useful for evaluating myocardial and LV performance, and especially for inotropism and lusitropism. Recently, we found that half-logistic (h-L) functions provide better fits for the two partial rising and two partial falling phases of the isovolumic LV pressure curve compared to mono-exponential (m-E) functions, and that the h-L time constants for the four sequential phases are superior inotropic and lusitropic indices com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The experimental procedures have been previously described in detail [4,6,7]. In short, seven albino rabbits (Japan White; body weight 2.0-2.5 kg) and 15 mice (C57BL/6; body weight 25-30 g) were anesthetized with intravenous (1.5-2.0 mg/kg) and intraperitoneal (15-20 mg/kg) pentobarbital sodium, respectively.…”
Section: Surgical Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedures have been previously described in detail [4,6,7]. In short, seven albino rabbits (Japan White; body weight 2.0-2.5 kg) and 15 mice (C57BL/6; body weight 25-30 g) were anesthetized with intravenous (1.5-2.0 mg/kg) and intraperitoneal (15-20 mg/kg) pentobarbital sodium, respectively.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…To maximize the amount of useful information extracted from the CaT, myocardial tension, and LV pressure waveforms, many investigators have attempted to curve-fit the waveforms by using various mathematical models. We previously found that the half-logistic (h-L) function, which is a half-curve of a non-linear sigmoid logistic function with a boundary at the inflection point, curve-fits the first half of the ascending phases of (1) the isometric myocardial tension curve from twitch stimulation to the maximum of the first-order time derivative of tension (dF/dt max ) [4] and (2) the isovolumic LV pressure curve from the point corresponding to QR on the electrocardiogram (ECG) to the maximum of the first-order time derivative of LV pressure (dP/dt max ) [5] better than the mono-exponential (m-E) function. The first half of the ascending phase of the CaT curve (faCaT) is expected to change in parallel with the amplitudes and time courses of the myocardial tension and LV pressure curves.…”
Section: Introductionmentioning
confidence: 99%